PERBANDINGAN CAPAIAN PEMBELAJARAN ANTARA METODE EKSPOSITORI DAN METODE DEMONSTRASI DALAM PELAJARAN BIOLOGI DI SMAN2 LANGSA - Roida Lisnawati Simamora; Elfrida Elfrida; Tri Mustika Sarjani (Bioedukasi Jurnal Pendidikan Biologi, 2026)
This study aims to determine the comparison of student learning outcomes applied with the expository method and the demonstration method in biology learning at SMA N 2 Langsa. This study is an experimental study with a pretest posttest control group design. The research sample consisted of classes X E and X G with a total of 60 students. The results showed that there was a comparison of student learning outcomes between the expository method and the demonstration method. The average posttest score of the demonstration class was 82.5 (high) and the expository class was 75.9 (high) so that the difference between the two classes was 6.6. While the average pretest score of the demonstration class was 45.1 (low) and the expository class was 41.7 (low) so that the difference between the two classes was 3.4 with a hypothesis test value of t count > t table or 3.121 > 2.001. Based on these results, it can be concluded that Ha is accepted and Ho is rejected, which means there is a comparison of student learning outcomes between the expository method and the demonstration method in biology learning at SMAN 2 Langsa. A significant comparison in the posttest results shows that the demonstration method is better than the expository method.Kata kunci: hasil belajar, metode demonstrasi, metode ekspositori